Platelet/lymphocyte ratio was associated with impaired myocardial perfusion and both in-hospital and long-term adverse outcome in patients with ST-segment elevation acute myocardial infarction undergoing primary coronary intervention - Toprak, Cuneyt; Tabakci, Mehmet M.; Simsek, Zeki; Arslantas, Ugur; Durmus, Halil I.; Ocal, Lutfi; Demirel, Muhittin; Ozturkeri, Burak; Ozal, Ender; Kargin, Ramazan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Platelet/lymphocyte ratio (PLR) has been shown to be an inflammatory and thrombotic biomarker for coronary heart disease, but its prognostic value in ST-segment elevation myocardial infarction (STEMI) has not been fully investigated. Aim: To investigate the relationship between PLR and no-reflow, along with the in-hospital and long-term outcomes in patients with STEMI. Material and methods : In the present study, we included 304 consecutive patients suffering from STEMI who underwent primary percutaneous coronary intervention (p-PCI). Patients were stratified according to PLR tertiles based on the blood samples obtained in the emergency room upon admission. No-reflow after p-PCI was defined as a coronary thrombolysis in myocardial infarction (TIMI) flow grade ≤ 2 after vessel recanalization, or TIMI flow grade 3 together with a final myocardial blush grade (MBG) < 2. Results : The mean follow-up period was 24 months (range: 22–26 months). The number of patients characterized with no-reflow was counted to depict increments throughout successive PLR tertiles (14% vs. 20% vs. 45%, p < 0.001). In-hospital major adverse cardiovascular events and death increased as the PLR increased (p < 0.001, p < 0.001). Long-term MACE and death also increased as the PLR increased (p < 0.001, p < 0.001). Multivariable logistic regression analysis revealed that PLR remained an independent predictor for both in-hospital (OR = 1.01, 95% CI: 1.00–1.01; p = 0.002) and major long-term (OR = 1.01, 95% CI: 1.00–1.01; p < 0.001) adverse cardiac events. Conclusions : Platelet/lymphocyte ratio on admission is a strong and independent predictor of both the no-reflow phenomenon and long-term prognosis following p-PCI in patients with STEMI.